Cyanobacterium producing cylindrospermopsin cause histopathological changes at environmentally relevant concentrations in subchronically exposed tilapia (Oreochromis niloticus). Issue 3 (2nd September 2013) - Guzmán‐Guillén, Remedios; Prieto, Ana I.; Moreno, Isabel; Vasconcelos, Vitor M.; Moyano, Rosario; Blanco, Alfonso; Cameán Fernandez, Ana M.
ABSTRACT The acute toxicity of cylindrospermopsin (CYN) has been established in rodents, based on diverse intraperitoneal an oral exposure studies and more recently in fish. But no data have been reported in fish after subchronic exposure to cyanobacterial cells containing this cyanotoxin, so far. In this work, tilapia (Oreochromis niloticus) were exposed by immersion to lyophilized Aphanizomenon ovalisporum cells added to the aquaria using two concentration levels of CYN (10 or 100 μg CYN L−1) and deoxy‐cylindrospermopsin (deoxy‐CYN) (0.46 or 4.6 μg deoxy‐CYN L−1), during two different exposure times: 7 or 14 d. This is the first study showing damage in the liver, kidney, hearth, intestines, and gills of tilapia after subchronic exposure to cyanobacterial cells at environmental relevant concentrations. The major histological changes observed were degenerative processes and steatosis in the liver, membranous glomerulopathy in the kidney, myofibrolysis and edema in the heart, necrotic enteritis in the gastrointestinal tract, and hyperemic processes in gill lamellae and microhemorrhages. Moreover, these histopathological findings confirm that the extent of damage is related to the CYN concentration and length of exposure. Results from the morphometric study indicated that the average of nuclear diameter of hepatocytes and cross‐sections of proximal and distal convoluted tubules are useful to evaluate the damage induced by CYN in the main targets of toxicity. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 261–277, 2015.